MANAGEMENT OF ECONOMIC RISKS IN TRANSPORT - V. Savchenko-Belsky; M. Maltseva (Вестник университета, 2016)
The article considers the essence of the economic risks of transport companies, features of risk management in the transport sector. Selected problems of managerial decision-making under uncertainty. Deals with the analysis and risk assessment. The necessity of a systematic approach to risk management in transport.